PENGARUH PENGETAHUAN AKUNTANSI DAN PERILAKU KEUANGAN TERHADAP KINERJA MANAJERIAL UMKM MAKANAN DI SIDOARJO - Hoirul Ummah; Siti Rosyafah; Masyhad (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2021)
MSMEs are the driving sector of the economy, but currently MSMEs have not been able to optimize their business managerial performance, this cannot be separated from the lack of accounting knowledge and financial behavior owned by MSME owners. This study aims to determine the effect of accounting knowledge and financial behavior on managerial performance in food SMEs in Sidoarjo. The formulation of the problem in this study is whether accounting knowledge, financial behavior simultaneously and partially affect managerial performance, and which of accounting knowledge and financial behavior has a dominant influence on managerial performance of food SMEs in Sidoarjo. The sample of this study used 30 food SMEs in Sidoarjo. This study is a quantitative study, using primary data obtained through the distribution of questionnaires and tested with validity, reliability, F-test and t-test using the SPSS application. The results showed that simultaneously and partially accounting knowledge and financial behavior had a significant effect on managerial performance. The variable that reaches the dominant value is financial behavior